Development of Mathematics E-LKPD with Flat Building Materials Using the Wizer.Me Website Application to Support Differentiated Learning - Apriani, Rintan; Pamungkas, Aan Subhan; Rakhman, Patra Aghtiar (Jurnal Pendidikan Amartha, 2025)
This research aims to determine the feasibility and determine students' responses to the use of E-LKPD mathematics learning media with flat building materials with the wizer.me website application to support differentiated learning in class V elementary schools. This research uses a Research and Development (RD) approach. The subjects in this research were 20 class V students. The research results show that in terms of feasibility, based on media expert validation, an average percentage score of 95% was obtained in the "Very feasible" category. The validation results from material experts obtained an average percentage score of 88.18% in the "Very feasible" category. Linguist validation results obtained an average percentage score of 87.27% in the "Very worthy" category. Based on the validation assessment, the experts obtained an average score from the expert team's assessment of 90.15%, this score was included in the "Very Decent" category. The results of product trials on class V students at SDN Jakung obtained an average score of 94%, indicating that the students' response to the use of E-LKPD mathematics learning media was in the "Very Good" category. Based on the research results, it can be concluded that the E-LKPD mathematics learning media with flat shape material with the wizer.me website application developed for fifth grade elementary school students is very suitable for use in supporting differentiated learning.